Asymptotics of elliptic and parabolic PDEs : and their Applications in Statistical Physics, Computational Neuroscience, and Biophysics /: and their Applications in Statistical Physics, Computational Neuroscience, and Biophysics. (2018) - Holcman, David; Schuss, Zeev, 1937-
No abstract available